National Judicial Reporting Program, 2000 ([Verlag nicht ermittelbar], 2003)
This data collection provides detailed information on the sentences and characteristics of convicted felons based on data collected from state courts. The 2000 survey was based on a sample of 344 counties selected to be nationally representative. The collection contains sociodemographic information such as age, race, and sex of the felon. Types of offenses committed include homicide, rape, and robbery. Adjudication variables referring to the process between arrest and sentencing are also a part of this dataset. Data can be analyzed at the national level or by individual counties.